Kesiapan Implementasi Knowledge Sharing & Transfer (KS&T) dalam pembelajaran di Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto - Arief, Mochamad Budi (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
Higher education as a sub-system of the national education system has a strategic role that includes educating the nation's life and advancing science and technology. Universities as an institution that has a strategic role in achieving a generation of excellence and quality in the development of Science and Technology, so as to compete in the global era and digital today. The purpose of this research is: to describe readiness implementation of Knowledge Sharing & Transfer (KS & T) in learning at Tarbiyah High School of Raden Wijaya Mojokerto. This research uses "Library Research" The research data used is secondary data. Data collection techniques used by the authors in this study is the documentation. Data processing is done by conducting the activity of review, verification and reduction, grouping and systematization, and interpretation or interpretation so that a phenomenon has social, academic, and scientific value. While data analysis in this research done during and after collecting data by using descriptive-critical-comparative method, and method of content analysis (content analysis). From the explanation described earlier, it was concluded: 1) Successful implementation of knowledge sharing and knowledge transfer did not escape the selection of appropriate strategies in its application. 2) Implementation of knowledge sharing and knowledge transfer is still hampered by human resources problems besides quality and quantity.